Assessing Risk Management Implementation in Islamic Gold Financing: The Case of Gadai Emas Syariah - Habibulloh; Eka Hanum Maulida (Business and Applied Management Journal, 2024)
This study aims to analyze and review the procedures of sharia gold pawn, the risks that affect sharia gold pawn products, and the implementation of risk management on these products at Baitul Maal Wa Tamwil (BMT). This study is based on the importance of understanding how sharia gold pawn operates and managing the risks that arise, especially in the context of BMT which has an important role in supporting the sharia economy. This study uses a qualitative approach with a case study research type. Data were collected through observation, interviews, and documentation, with the main informants being the Head of BMT and employees (tellers) at BMT. Source triangulation techniques were used to ensure the validity of the data. The results of the study indicate that the sharia gold pawn procedure at BMT involves submitting identity, bringing collateral, filling out a pawn form, assessing collateral, and disbursing loans. There are three main risks that affect sharia gold pawn, namely operational risk, credit risk, and market risk. The implementation of risk management in sharia gold pawn in BMT is quite good, with stages including risk identification, risk measurement, risk monitoring, and risk control. These stages are carried out as a form of BMT's caution in maintaining the sustainability of sharia gold pawn products. This study contributes to providing a deeper understanding of the risk management process in sharia financing, especially in the gold pawn sector.